Research on establishing size system and designing shoe lasts for female diabetics in Vietnam - Cao, Thi Kien Chung; Bui, Van Huan (JST: Engineering And Technology For Sustainable Development, 2021)
Shoe lasts are tool for designing and manufacturing shoes, mainlly deciding on the shape, fit and comfort of the shoe. The paper presents the method and results of setting up the size system and designing shoe lasts for female diabetics based on the results of studying foot shape and size, requirements of shoes for diabetics. The parameters of 7 shoe last sizes in length with 3 sizes of width/girth according to the Mondopoint international size system are built. The parameters of shoe lasts for female diabetics are much bigger than those for normal women, especially the ball is bigger than 24 mm, the ball width is larger than 6 mm. Using shoe last design software, 3D printing technology has designed and manufactured shoe lasts, that meet the requirements to make shoes for female diabetics in Vietnam.